The Mediterranean at the Dawn of the Third Millennium - Leoluca Orlando (Nordicum-Mediterraneum, 2024)
The Mediterranean, after the end of the Cold War and the massacres of 11.9.2001 in New York and 7.10.2023 in Israel, is at the center of new conflicts and international imbalances. The crisis of Western hegemony is confirmed and intertwined with growing migratory flows, desertification and poverty produced by new financial selfishness and climate change, genocides and wars involving old and new forms of colonialism. Also, the Mediterranean is confronted with the new protagonism of the South of the world. “Our Sea” is a symbolic place for new conceptions of Identity, Race and God, and of the desire for freedom from old and new fears.